Respostas
respondido por:
2
x² -3x - 4=0
Soma(x' + x")=-b/a = 3
Produto(x' * x")=c/a = -4
x'= 4
x"= -1
S{-1,4}
Soma(x' + x")=-b/a = 3
Produto(x' * x")=c/a = -4
x'= 4
x"= -1
S{-1,4}
respondido por:
1
x^2 - 3x - 4 = 0
a = 1
b = -3
c = -4
∆ = b^2 - 4ac
∆ = (-3)^2 - 4 . 1 . (-4)
∆ = 9 + 16
∆ = 25
x = -b +-√∆/2a
x = (3 +-√25)/2
x = (3 +-5)/2
x' = (3 + 5)/2
x' = 8/2
x' = 4
x'' = (3 - 5)/2
x'' = -2/2
x'' = -1
S = {4,-1}
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás